2004
DOI: 10.1128/aem.70.2.771-780.2004
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Cu Environments in the CyanobacteriumAnabaena flos-aquaeby X-Ray Absorption Spectroscopy

Abstract: Whole cells and peptidoglycan isolated from cell walls of the cyanobacterium Anabaena flos-aquae were lyophilized and used at pH 2 and pH 5 in Cu(II) binding studies. X-ray absorption spectra measured at the Cu K-edge were used to determine the oxidation states and chemical environments of Cu species in the whole-cell and peptidoglycan samples. In the whole-cell samples, most of the Cu retained at both pH values was coordinated by phosphate ligands. The whole-cell fractions contained significant concentrations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
20
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 69 publications
(77 reference statements)
3
20
0
Order By: Relevance
“…The concentrations of copper binding to γ-globulin did not surpass 20-24 µM and were below the concentrations toxic for bacterial and human cells [5,10,12] or destabilizing biomacromolecules by many folds [2]. Hence, γ-globulin, which bound copper under conditions of metal exchange, is nontoxic and will not promote cleavage of structures (cells and biopolymers) reacting with it (if we rule out the possibility that the protein releases all bound cations simultaneously into the local microenvironment).…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…The concentrations of copper binding to γ-globulin did not surpass 20-24 µM and were below the concentrations toxic for bacterial and human cells [5,10,12] or destabilizing biomacromolecules by many folds [2]. Hence, γ-globulin, which bound copper under conditions of metal exchange, is nontoxic and will not promote cleavage of structures (cells and biopolymers) reacting with it (if we rule out the possibility that the protein releases all bound cations simultaneously into the local microenvironment).…”
Section: Resultsmentioning
confidence: 96%
“…We previously showed that γ-globulin fraction proteins interact with copper cations in solution. Obvious changes in the protein conformation manifesting (depending on copper concentration) by unfolding of the molecule into extramolecular space or by compactization of the globule indicate that the metal is bound by sites located on the surface of γ-globulin molecule or in its inter-domain space [8,9].Binding and subsequent retention of copper by the biopolymer molecule can cause changes determined by the chemical properties of cations (toxicity of copper in supraphysiological concentrations [5,10,12], redox activity of metal capable of inducing cleavage or destabilization of biological structures binding it [1,2]) and by physicochemical changes in immunoactive serum proteins under physiological conditions (manifestation of new effector properties in the proteins which bound cations and transition of this protein into a new conformation status) [3,9].We studied conformation changes in γ-globulin during copper cation binding and evaluated the parameters of this binding. …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Copper-binding sites are widely presented on biomacromolecules [10]. In antibodies the complementary sites of variable regions form 11 sites for copper and zinc binding [15].…”
Section: Resultsmentioning
confidence: 99%
“…This ability is of great interest because of its potential use in the removal of metals from contaminated water or soil, as well as for the recovery of precious metals (Au, Pt, Pd, Rh) from industrial wastes. Several genera of microorganisms have been used for such purposes [30][31][32][33][34][35][36].…”
Section: Interaction Of Slps With Metalsmentioning
confidence: 99%